1990
DOI: 10.1139/f90-241
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Wind on the Recruitment of Canadian Arctic Cisco (Coregonus autumnalis) into the Central Alaskan Beaufort Sea

Abstract: The recruitment of age 0+ Arctic cisco (Coregonus autumnalis) from Canada into the Prudhoe Bay, Alaska, area for the period 1981–88 was compared with summer wind data collected at Barter Island, Alaska. Four years of poor recruitment (1981, 1982, 1984, and 1988) were characterized by winds with net easterly components [Formula: see text] for the period 1 July—15 August. Four years in which moderate to strong recruitment occurred (1983, 1985, 1986, and 1987) were characterized by winds with net easterly compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 1 publication
1
18
0
Order By: Relevance
“…The importance of wind events is generally unexplored for the early life stages of freshwater fishes, but it is well recognized for marine fish larvae. Wind-driven currents serve an important role regulating the survival of marine larvae such as Arctic cisco Coregonus autumnalis along the Beaufort Sea coast, where strong recruitment is linked to years with high winds that transport larvae (Fechhelm and Griffiths 1990). Wind-induced currents also influence other Great Lakes larvae, such as those of cisco Coregonus artedi in Lake Superior, by transporting them from spawning areas (Hoff 2004).…”
Section: Inferences About Recruitment In Large Freshwater Systemsmentioning
confidence: 99%
“…The importance of wind events is generally unexplored for the early life stages of freshwater fishes, but it is well recognized for marine fish larvae. Wind-driven currents serve an important role regulating the survival of marine larvae such as Arctic cisco Coregonus autumnalis along the Beaufort Sea coast, where strong recruitment is linked to years with high winds that transport larvae (Fechhelm and Griffiths 1990). Wind-induced currents also influence other Great Lakes larvae, such as those of cisco Coregonus artedi in Lake Superior, by transporting them from spawning areas (Hoff 2004).…”
Section: Inferences About Recruitment In Large Freshwater Systemsmentioning
confidence: 99%
“…In Alaska, C. autumnalis make long‐distance movements from spawning to rearing locations and smaller scale annual marine migrations between feeding and overwintering habitats. Coregonus autumnalis captured in Alaskan waters are the progeny of fish that spawn in tributaries of the Mackenzie River, Canada (Craig, 1989; Fechhelm & Griffiths, 1990). Spawning and hatching success has not been extensively studied in Canada, but hatching is thought to coincide with spring freshet and river break‐up as it does with other coregonids (Næsje et al , 1986, 1995; Urpanen et al , 2005).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Fechhelm and Griffiths (1990) studied the 600-700 km westward transport of Arctic cisco (Coregonus autumnalis) larvae along the Alaskan and Canadian Beaufort Sea coast. They found that years of moderate to high recruitment were associated with strong easterly winds during summer, and years of poor recruitment occurred when easterly winds were weak.…”
Section: Discussionmentioning
confidence: 99%